Corporate Social Responsibility dan Ketahanan Perusahaan Dalam Menghadapi Pandemik di Asia Tenggara - Asniati Bahari (Jurnal Akademi Akuntansi, 2023)
This study aims to find empirical evidence regarding the influence of CSR on corporate resilience in facing the COVID-19 pandemic in Southeast Asia during the first and second waves of the pandemic. The independent variable in this research is the company's CSR which consists of economic, environmental and social disclosures, while the dependent variable is company resilience. There were 175 companies as research samples in the first wave and 176 in the second wave. Data is obtained from sustainability reports and annual reports published by each company through its official website. Using SmartPLS 3.3.9, it was found that, both in the first and second waves of COVID-19, overall CSR had a positive effect on corporate resilience. In the first wave, disclosure of economic topics had a positive effect on corporate resilience, but disclosure of environmental and social topics had a negative effect. In the second wave, disclosure of social topics had a positive effect on corporate resilience, but disclosure of economic and environmental topics had a negative effect. The implications of this research show that companies need to disclose their business continuity activities during a pandemic to increase corporate resilience. With the longer the pandemic lasts, social activities are more important than economic and environmental activities. The results of this study can enrich knowledge in the field of sustainability accounting which is useful for company management in managing corporate sustainability and also for investors in choosing their investment objects.